Μελέτη μεταβολικών διαδρομών των μικροοργανισμών της αναερόβιας κοκκώδους ιλύος κατά την μεθανογένεση έχοντας ως μοναδική πηγή άνθρακα το CO2 και μεταλλικό σίδηρο - Ανδρονίκου, Μαρία (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
This study investigates exactly which metabolic pathways are favored by a new approach where there is utilization and conversion of CO2 to CH4 by using Zero Valent Iron (ZVI) and anaerobic granular sludge. Numerous studies have used ZVI to stimulate the anaerobic digestion of waste and wastewater. Up to date however, little research has been done on the use of ZVI and anaerobic granular sludge for the conversion of CO2 as a sole carbon substrate to CH4. The results showed that at initial pH of 6 under daily pH regulation contributed to substantial CH4 production. For the most effective concentration value of ZVI for 2 g L-1 anaerobic granular sludge was the value of 100 g L-1. To point out the microbial pathways for CO2 conversion to CH4, the following inhibitors were independently added: antibiotics for bacteria inhibition, BES for methanogens inhibition and CHCl3 for inhibition of bacteria and methanogens. Results showed that when antibiotics were added, they did not have any negative effect on CO2 conversion to CH4. This demonstrates that CO2 is converted to CH4 through hydrogenotrophic methanogens and the contribution of homoacetogens was negligible. The anaerobic granular sludge exposed to 100 g L-1 ZVI (produced 31 mL CH4 at 288 h) has generated formic acid (172 mg L-1) as the main volatile fatty acid in the first 72 h and then it was gradually decreased. The exposure of granular sludge to ZVI and BES resulted in no generation of CH4 and accumulation of VFAs so after 192 h the formic acid, acetic acid and propionic acid concentration was 600 mg L-1, 427 mg L-1 and 76 mg L-1 respectively.
Keywords: Αnaerobic granular sludge; CO2 utilization; Ηomoacetogenesis; Ηydrogenotrophic methanogens; Zero Valent iron; Μethane; Αναερόβια κοκκώδης ιλύς; Χρήση διοξειδίου του άνθρακα; Στοιχειακός σίδηρος; Υδρογονοτρόφοι μεθανογόνοι; Οξικογένεση; Μεθάνιο